Manhood and the Militia Myth: Masculinity, Class and Militarism in Ontario, 1902-1914 - O'Brien, Mike (Labour / Le Travail, 1998)
The period between 1902 and 1914 witnessed a flourishing of interest in military matters in Ontario. Military activity in the province centred primarily on the Canadian Militia, a part-time citizen army in which thousands of young men participated. Contemporary advocates of military service saw the Militia as a "school of manliness" which would instill a variety of civic virtues in its members. This paper examines the question of working-class participation in the Militia, looking in particular at how the concept of "masculinity" interacted with issues of class in an industrial-capitalist society. It identifies a number of attractions which Militia service held for working-class recruits; it also points to important contradictions between gendered social ideals and class-based reality. In particular, the difficult relationship between the Militia and organized labour, and the incompatability of the "rough culture" of the working classes with middle-class ideals of "manliness," are discussed in depth. On a theoretical level, it suggests that while "masculinity" provides a vital basis for understanding the history of the Militia in Ontario, it cannot be seen in isolation from other factors, most notably class relations.